Case Report: Facial and eye injury following a fridge cylinder gas explosion - Monsudi Kehinde Fasasi; Ehumadu Chioma Nwabugwu; Gero Na'allah Rumu (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2017)
Fridge cylinders contain liquefied petroleum gas (LPG), an inflammable gas of mixture of propane and butane [1]. It's colourless but odourised to give warning during leakage. Injury from accidental fridge cylinder explosion is similar to any other blast injuries in terms of the release of hot gases, blast wave and metal fragments resulting in extensive skin burns, abrasions, penetrating injury and tissue loss [2-4]. Ocular trauma following gas cylinder explosion is rare however, Babar et al reported 20% of ocular trauma to be secondary to gas cylinder and battery explosion [2]. To our knowledge, this is the first case of facial and eye injury following a fridge cylinder gas explosion reported in the literature.